"Ξεθάβουν τώρα τα αγάλματα": οι αισθητήριες αρχαιολογίες του Γιώργου Σεφέρη. (Τιμητικός Τόμος για τη Στέλλα Δρούγου, 2016)
In June 1946 George Seferis, the eminent Greek poet who was going to become the Nobel-laureate patriarch of Greek modernist poetry by 1963, witnessed the re-excavation of the statues and vases until then hidden in the vaults of the National Museum in Athens in order to prevent their damage, or looting, by the Germans during the occupation. As he observes the bronze statue of Zeus, a fifth-century BC work that is still considered one of the masterpieces in the Museum’s collection and of Greek art at large, the poet fantasizes the god’s lovemaking with a woman whom Seferis himself “would love”, as he unashamedly informs us in his diary from that day. In the paper, I use the concept of homosociality in order to explore the ways in which Seferis and many of his contemporaries view classical antiquity and proceed to deploy it as a bio-political tool in order to claim a centralized role in Greek intellectual and political life. To this end, I re-visit Seferis’s two chief “archaeological” poems –The King of Asine and Engomi – in an effort to investigate the ways in which his sensory archaeologies manifest themselves.